2016
DOI: 10.1038/ncomms13729
|View full text |Cite
|
Sign up to set email alerts
|

Radiative cooling to deep sub-freezing temperatures through a 24-h day–night cycle

Abstract: Radiative cooling technology utilizes the atmospheric transparency window (8–13 μm) to passively dissipate heat from Earth into outer space (3 K). This technology has attracted broad interests from both fundamental sciences and real world applications, ranging from passive building cooling, renewable energy harvesting and passive refrigeration in arid regions. However, the temperature reduction experimentally demonstrated, thus far, has been relatively modest. Here we theoretically show that ultra-large temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
449
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 709 publications
(454 citation statements)
references
References 24 publications
5
449
0
Order By: Relevance
“…According to (5), solar absorption and non-radiative heat transfer act as parasitic cooling losses, thereby reducing the overall cooling efficiency and increasing the cooling time to reach thermal equilibrium. Remarkably, it has been experimentally demonstrated that significant temperature reduction up to 40 K below ambient has been reached by radiative cooling within 1 h [47]. For systems with greater heat loads (e.g.…”
Section: Principle Of Coolingmentioning
confidence: 99%
“…According to (5), solar absorption and non-radiative heat transfer act as parasitic cooling losses, thereby reducing the overall cooling efficiency and increasing the cooling time to reach thermal equilibrium. Remarkably, it has been experimentally demonstrated that significant temperature reduction up to 40 K below ambient has been reached by radiative cooling within 1 h [47]. For systems with greater heat loads (e.g.…”
Section: Principle Of Coolingmentioning
confidence: 99%
“…25 Achieving such low temperatures requires high vacuum to minimize parasitic conduction and convection. 21 If such parasitic mechanisms are present, expanding the bandwidth of thermal emission is likely to be benecial despite the increase in sky radiation absorption as shown in Figure 4b.…”
Section: Acs Photonicsmentioning
confidence: 99%
“…Thus, expanding the spectral range of high emissivity can be benecial under some circumstances. 21,25 For a cooler temperature of 300 K, Case 1 achieves a cooling power density 158 Wm -2 , 43 Wm -2 higher than Case 2.…”
Section: Acs Photonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of global water cycle, moderate global temperature, humidity, and precipitation may be attainable through the tunable plant transpiration. Moreover, photothermal conversion shows the potential as the regulator of the nature, besides the emerging applications, such as radiative cooling,42, 43, 44, 45 thermophotovoltaics,46, 47, 48, 49 water purification,10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 seawater desalination,24, 25, 26, 27 and power generation 28, 29…”
mentioning
confidence: 99%